2013
DOI: 10.1177/1476127013502465
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting alternative explanations for the consequences of category spanning: A study of restaurant reviews and menus in San Francisco

Abstract: Recent literature on organizational category spanning demonstrates that organizations that span multiple categories on average suffer social and economic disadvantages in markets. While multiple mechanisms have been proposed to explain this finding, most studies do not test directly nor contrast these mechanisms. In this article, we contrast two of the main mechanisms proposed in the literature: the audience-side typicalitybased explanation (category spanners are atypical of each categories spanned) and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 63 publications
1
68
0
Order By: Relevance
“…We cannot, however, tell these cases apart in our data. Future work is needed to address this distinction both theoretically and empirically, for example, by analyzing restaurant menus-see Kovács and Johnson (2014). Relatedly, we argued that spanning restaurants and books get devalued because they confuse audience members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot, however, tell these cases apart in our data. Future work is needed to address this distinction both theoretically and empirically, for example, by analyzing restaurant menus-see Kovács and Johnson (2014). Relatedly, we argued that spanning restaurants and books get devalued because they confuse audience members.…”
Section: Discussionmentioning
confidence: 99%
“…Admittedly, the rating might relate to multiple dimensions of value, such as food quality or service for restaurants (Kovács and Johnson (2014) found that the most important dimension is food quality), and the quality of the writing or the reputation of the author in the case of books. We do not attempt to disentangle these dimensions here.…”
Section: Notesmentioning
confidence: 99%
“…The higher an object's typicality, the higher the probability that the agent regards it as an instance of the associated concept (Rosch and Mervis 1975;Tversky and Gati 1978). For example, restaurants with similar menus get classified alike (Kovács and Johnson 2014). This means that whether an object gets assigned a label declines monotonically with its distance from the schema/prototype.…”
Section: Categorization: Assigning Labels To Producersmentioning
confidence: 99%
“…15 Parts of these data have been used previously in Hannan (2010, 2015) and Kovács and Johnson (2014), who demonstrate that restaurants that span (distant) categories receive lower ratings. we were to use the prior approach of merely counting the number of genres applied to an object.…”
Section: Measurementmentioning
confidence: 99%